Comprehensive molecular characterization of Methylobacterium extorquens AM1 adapted for 1-butanol tolerance. Issue 1 (December 2016) - Hu, Bo; Yang, Yi-Ming; Beck, David; Wang, Qian-Wen; Chen, Wen-Jing; Yang, Jing; Lidstrom, Mary; Yang, Song
Abstract Background The toxicity of alcohols is one of the major roadblocks of biological fermentation for biofuels production.Methylobacterium extorquens AM1, a facultative methylotrophic α-proteobacterium, has been engineered to generate 1-butanol from cheap carbon feedstocks through a synthetic metabolic pathway. However, M. extorquens AM1 is vulnerable to solvent stress, which impedes further development for 1-butanol production. Only a few studies have reported the general stress response ofM. extorquens AM1 to solvent stress. Therefore, it is highly desirable to obtain a strain with ameliorated 1-butanol tolerance and elucidate the molecular mechanism of 1-butnaol tolerance inM. extorquens AM1 for future strain improvement. Results In this work, adaptive laboratory evolution was used as a tool to isolate mutants with 1-butanol tolerance up to 0.5 %. The evolved strains, BHBT3 and BHBT5, demonstrated increased growth rates and higher survival rates with the existence of 1-butanol. Whole genome sequencing revealed a SNP mutation atkefB in BHBT5, which was confirmed to be responsible for increasing 1-butanol tolerance through an allelic exchange experiment. Global metabolomic analysis further discovered that the pools of multiple key metabolites, including fatty acids, amino acids, and disaccharides, were increased in BHBT5 in response to 1-butanol stress. Additionally, the carotenoid synthesis pathway was significantly down-regulated in BHBT5. Conclusions We successfully screened mutants resistant to 1-butanol and provided insights into the molecular mechanism of 1-butanol tolerance inM. extorquens AM1. This research will be useful for uncovering the mechanism of cellular response ofM. extorquens AM1 to solvent stress, and will provide the genetic blueprint for the rational design of a strain ofM. extorquens AM1 with increased 1-butanol tolerance in the future.